We Are Already Dead. Long May We Live!: Death as Event in Koos Prinsloo's Metropolis - Gray, Chantelle (Journal of literary studies (Pretoria, South Africa), 2019)
In this article, I think about death as "event" by reading Koos Prinsloo through the three syntheses of time - Habit, Mnemosyne and Thanatos - as explicated by philosopher Gilles Deleuze in Difference and Repetition, as well as work done with his sometimes co-author, Félix Guattari. I argue that Prinsloo's oeuvre provides a critical and clinical function that can provide methods for releasing jouissance so that the death drive can be re-directed. Thus, whereas the critical function engages literary figures, styles and ways of being, as well as Kant's understanding of critique, the clinical provides a symptomatology of life potentiality in a given work. Together, these function to identify the genesis of life as a creative force and, in so doing, restores healthy living.